American presidents : year by year - Nelson, Lyle Emerson, 1924- (Sharpe Reference, 2004)
This fascinating multi-volume set illuminates the panorama of American history through the personal and professional stories of the nation's presidents. Arranged chronologically, and covering George Washington to George W. Bush, it juxtaposes the lives of each year's current, former, and future living presidents against each other and the historical backdrop of their times. Each chapter opens with a summary of the year and describes the major issues and events the incumbent president faced. Separate sections within each chapter - ""Former Presidents"" and ""Future Presidents""--Detail importa